Bamboo Kraft Pulp Black Liquor as a Renewable Source of Value-Added Carbon Dots - Xiaolong Qiao; Shixing Wang; Qiulian Liu; Yuanming Zhang; Guangting Han; Haoxi Ben; Wei Jiang; Haiguang Zhao; Yan Song (Nanomaterials)
China is the country with the most abundant bamboo resources in the world. Using bamboo as a raw material for pulping and papermaking can save a lot of wood and protect forests. Bamboo pulping enterprises mostly adopt sulfate processes to produce a large amount of black liquor (BL), which contains monosaccharides, polysaccharides, oligosaccharides, pectin, lignin, etc. The utilization of the high-value organic matter is of great economic and environmental significance. In this study, blue-green carbon dots (C-dots) were prepared from bamboo (Lingnania chungii) kraft pulp BL using a hydrothermal method. The changes in carbohydrate content in BL in relation to hydrothermal temperature and hydrothermal time were discussed in detail. Then, a series of characterizations of BL-C-dots, prepared under one of the hydrothermal conditions (180 °C, 6 h), were performed and the BL-C-dots showed an excitation-dependent photoluminescence (PL) spectrum and a quantum yield (QY) of 2.9% in an aqueous solution. Finally, the as-prepared BL-C-dots were successfully used as fluorescent materials to develop an anti-counterfeiting code. The fluorescent code exhibited a clear outline, an excitation-tunable color, good stability, and high security, showing great anti-counterfeiting potential and realizing the high-value utilization of BL.